2017
DOI: 10.1186/s12933-017-0627-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma irisin is elevated in type 2 diabetes and is associated with increased E-selectin levels

Abstract: BackgroundIrisin is a hormone released mainly from skeletal muscle after exercise which increases adipose tissue energy expenditure. Adipocytes can also release irisin after exercise, acting as a local adipokine to induce white adipose tissue to take on a brown adipose tissue-like phenotype, suggesting that irisin and its receptor may represent a novel molecular target for the treatment of obesity and obesity-related diabetes. Previous reports provide conflicting evidence regarding circulating irisin levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 60 publications
(61 reference statements)
5
35
2
Order By: Relevance
“…Irisin has been identified as a novel myokine, which has been reported to be associated with the browning of white adipose tissue (WAT) and regulating energy balance, etc., [11]. Betatrophin has also been found to regulate β-cell proliferation, glucose/lipid homeostasis and autophagic flux [20]. Previous studies have shown that circulating ZAG, Irisin and Betatrophin concentrations were significantly reduced or elevated in patients with T2DM or PCOS, respectively, and were associated with IR [10][11][12][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Irisin has been identified as a novel myokine, which has been reported to be associated with the browning of white adipose tissue (WAT) and regulating energy balance, etc., [11]. Betatrophin has also been found to regulate β-cell proliferation, glucose/lipid homeostasis and autophagic flux [20]. Previous studies have shown that circulating ZAG, Irisin and Betatrophin concentrations were significantly reduced or elevated in patients with T2DM or PCOS, respectively, and were associated with IR [10][11][12][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Betatrophin has also been found to regulate β-cell proliferation, glucose/lipid homeostasis and autophagic flux [20]. Previous studies have shown that circulating ZAG, Irisin and Betatrophin concentrations were significantly reduced or elevated in patients with T2DM or PCOS, respectively, and were associated with IR [10][11][12][20][21][22]. In addition, a recent meta-analysis and other populations had indicated that serum irisin concentration in PCOS women were higher than that in healthy women, this elevaluation could be partly attributed to the BMI in PCOS patients [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paracrine adipokine induces the WAT to adopt a brown adipose tissue-like phenotype, but, concomitantly, it may lead to endothelial dysfunction and atheromatous lesions in patients with diabetes. Hence, irisin and its receptor may be new therapeutic targets in diabetes mellitus and obesity (40).…”
Section: Pvat and Atherosclerosismentioning
confidence: 99%
“…Up until now, the optimal irisin level in human has not been established, and controversial results about its levels in different pathological conditions have been observed. In fact, both decreased and increased irisin levels have been observed in DM, insulin resistance and metabolic syndrome [19][20][21][22][23]. If, from one side, irisin reduction might lead to some metabolic changes involved in the onset and progression of a disease, on the other side its up-regulation could be a consequence of an "irisin resistance" state and therefore an attempt to maximize the anti-obesity, anti-hyperglycemic and healthy effects of the molecule.…”
Section: Introductionmentioning
confidence: 99%